Curva hype cycle como ferramenta de apoio à decisão de investimento na transição energética - Freitas, Marcella Dias (2020)
The process of energy transition is imminent and inevitable. The intense technological development in recent years has contributed strongly to significant structural changes in the electricity sector. As part of these changes, can be mentioned, for example, the increase in distributed generation, the development of disruptive technologies, such as smart grids and smart homes, and the electrification of the transport sector. In this sense, the role of traditional electric companies will change, and way to adapt to this new structure is investing in cleantech startups that offer clean technology innovation products more efficiently and cheaper than large companies. This work has as main objective to offer a product to support decision making for investors, translated in the form of a technology maturity curve - Hype Cycle -, so that large companies can invest in cleantech startups through the modality of venture capital investments. From the results obtained in this work, it was possible to conclude that, although there are some criticisms to the methodology, the Hype Cycle curves described the level of maturity of the technologies evaluated sufficiently well for the current moment in Brazil. Thus, the methodology is confirmed as an important support tool for investor decision making, which now has more information to decide when to make its investments.